The mediating role of mindfulness and psychological resilience in the relationship between internalized stigma and caregiver burden among parents of children with Autism Spectrum Disorder - Ozturk, Ayfer (Frontiers Media Sa, 2026)
Background: Stigma surrounding Autism Spectrum Disorder (ASD) is prevalent, but limited studies have examined its negative psychological effects on parents of children with ASD and the potential protective factors in this family context. Moreover, no research has examined the mediating role of factors such as psychological resilience and mindfulness, that we think may consider potential buffers in the relationship between internalized stigma and caregiver burden which one of its negative consequences for these parents. The aim of this study is to investigate the mediating role of psychological resilience and mindfulness in the relationship between perceived caregiver burden and internalized stigma in parents of children with ASD and to provide a theoretical basis for studies aimed at reducing internalized stigma and caregiver burden in these parents. Methods: The study was conducted between March 2023 and January 2025 with a sample of 138 parents of children diagnosed with ASD receiving services from special education and rehabilitation centers. Data analysis included descriptive statistics, Pearson correlation, multiple linear regression, and Structural Equation Modeling (SEM) to assess mediation effects. For normally distributed data, Independent Samples t-test and One-Way ANOVA were applied to compare group differences. Results: The study found that parents had average total scores of 14.39 for resilience, 65.97 for internalized stigma, 55.59 for caregiver burden, and 52.93 for mindfulness. Caregiver burden was significantly higher among parents aged 20-25, those with lower income, and female parents. Additionally, having another child with a disability was associated with higher internalized stigma and lower resilience. Internalized stigma was significantly correlated with resilience, caregiver burden, and mindfulness (p < 0.001 for all). Psychological resilience (beta = 0.174) and mindfulness (beta = 0.254) were found to have significant indirect effects and partially mediated the relationship between internalized stigma and caregiver burden. Conclusion: These research findings indicate mindfulness and psychological flexibility are factors contributing to resilience against caregiver burden. Future interventions to reduce burden in caregivers of children with ASD might be improved by the inclusion of resilience and mindfulness training programs.
Keywords: Autism Spectrum Disorder (Asd); Caregiver Burden; Mindfulness; Parents; Resilience; Stigma